Critical Speed Analysis of Fibre Reinforced Composite Rotor Embedded with Shape Memory Alloy Wires - K. Gupta (International Journal of Rotating Machinery)
In the present analysis, the fundamental natural frequency of a Jeffcott and a two-mass rotor with fibre reinforced composite shaft embedded with shape memory alloy (SMA) wires is evaluated by Rayleigh's procedure. The flexibility of rotor supports is taken into account. The effect of three factors, either singly or in combination with each other, on rotor critical speed is studied. The three factors are: (i) increase in Young's modulus of SMA (NITINOL) wires when activated, (ii) tension in wires because of phase recovery stresses, and (iii) variation of support stiffness by three times because of activation of SMA in rotor supports. It is shown by numerical examples that substantial variation in rotor critical speeds can be achieved by a combination of these factors which can be effectively used to avoid resonance during rotor coast up/down.